Obtenção de plasma rico em plaquetas autólogo de coelhos com poucos leucócitos e hemácias - Andrade, Marina Greco Magalhães Guerra de (2014)
The objective was to develop a method to obtain an autologous rich plasma in platelets with few leukocytes and blood cells using the whole blood of rabbits submitted to two centrifugations. Blood was collected by intracardiac route 10.5mL and distributed into three tubes of blood sedimentation containing sodium citrate. The tubes with blood was submitted to centrifugation at 2,000 rpm (670,8G) for 20 minutes and the sedimentation columns were aspirated from each tube 1.000μL of plasma to reduce the volume of supernatant. It was aspirated the plasma above the ring of leukocytes and transferred it to another tube to centrifugate again at 2000 rpm (670.8 L) for 10 minutes. The platelet content in the bottom of the tube was resuspended and homogenized 1.000μL the supernatant plasma to form the PRP liquid (Group G1). The capacity of platelet activation was observed from the formation of a clot called PRP gel (group G2) when it was added 100mL of rabbit thromboplastin, calcium chloride 0.0125 mol /l and sodium chloride 0.1 mol / l of PRP 100mL liquid. The counting of the platelets, erythrocytes and leukocytes total number was done before and after centrifugations and they were performed in a veterinary automatic hematology analyzer. It was noted in G1, an increase of 61.58% in relation to platelet blood count to get the average concentration of 370 484 platelets / uL in PRP and were eliminated from the process 71% to 89% of leukocytes and erythrocytes. The evaluation by transmission electron microscopy identified in G1 that platelets showed morphological integrity preserved and individualized, with intact cell membrane, emission of pseudopods and centralization of granules and organelles. In G2, the platelets were grouped, with difficult to identify the intracytoplasmic structures of cell, membrane lysis, shedding of cytoplasmic granules into the extracellular place and the presence of fibrin. The method for obtaining an autologous plasma rich of platelets in rabbits is simple and reduce the number of leukocytes and blood cells and the platelets continue with a morphological and functional integrity.